2015
DOI: 10.1016/j.bmcl.2015.10.066
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Disubstituted and 1,3,3-trisubstituted adamantyl-ureas with isoxazole as soluble epoxide hydrolase inhibitors

Abstract: Adamantyl ureas are good soluble epoxide hydrolase (sEH) inhibitors; however they have limited solubility and rapid metabolism, thus limiting their usefulness in some therapeutic indications. Herein, we test the hypothesis that nodal substitution on the adamantane will help solubilize and stabilize the compounds. A series of compounds containing adamantane derivatives and isoxazole functional groups were developed. Overall, the presence of methyl on the nodal positions of adamantane yields higher water solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…COX-2 is highly expressed in inflammation and proliferative diseases, such as various cancers; therefore, it is a target to develop anti-inflammatory and antitumor agents . A recent study has demonstrated that coadministration of EETs and COX inhibitors exerts a better effect than the single administration of COX inhibitors to reduce LPS-induced pain and hypotension. , Accordingly, a series of sEH/COX-2 dual inhibitors based on the structural skeletons of celecoxib and t -AUCB ( 8 , Figure ) were designed, and it was found that 68 (PTUPB) displayed potent inhibitory activities against both sEH and COX-2. Molecular stimulation shows that PTUPB ( 68 ) forms hydrogen bond interactions with amino acid residues Asp333, Tyr381, and Tyr465 of human sEH, and His90 and Tyr335 of mouse COX-2.…”
Section: Seh Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 is highly expressed in inflammation and proliferative diseases, such as various cancers; therefore, it is a target to develop anti-inflammatory and antitumor agents . A recent study has demonstrated that coadministration of EETs and COX inhibitors exerts a better effect than the single administration of COX inhibitors to reduce LPS-induced pain and hypotension. , Accordingly, a series of sEH/COX-2 dual inhibitors based on the structural skeletons of celecoxib and t -AUCB ( 8 , Figure ) were designed, and it was found that 68 (PTUPB) displayed potent inhibitory activities against both sEH and COX-2. Molecular stimulation shows that PTUPB ( 68 ) forms hydrogen bond interactions with amino acid residues Asp333, Tyr381, and Tyr465 of human sEH, and His90 and Tyr335 of mouse COX-2.…”
Section: Seh Inhibitorsmentioning
confidence: 99%
“…77 In addition to the cyclohexyl group, an aromatic ring and an isoxazolyl group were also used as the replacement of the piperidinyl group at the right side of N-adamantyl-N′piperidinyl-ureas such as APAU (6) in view of their limited solubility and rapid metabolism (Figure 3), which reduced the mp of the inhibitors and should enhance the stability. 79 Despite the potent inhibitory activity observed in this series of compounds, such as 1-(adamant-1-ylmethyl)-3-{[5-(furan-2yl)isoxazol-3-yl]methyl}urea (10, AFMU) and 1-(adamant-1ylmethyl)-3-[(3-methylisoxazol-5-yl)methyl]urea (11, AMMU), their stability was not improved in HLM with nicotinamide adenine dinucleotide phosphate (NADPH). 79 The next step in sEH inhibitor development involved the optimization of the adamantyl-ureas via adding the substitution to the bridgehead of the adamantane to afford a library of this type compound (Figure 4).…”
Section: Seh Inhibitorsmentioning
confidence: 99%
“…One of the common strategies to overcome poor solubility is the introduction of polar groups outside of the main pharmacophore, a strategy which has been applied to sEH inhibitors by Kim et al 14 However, the evolutionary pathway in the design of urea sEH inhibitors went in the direction of creating non-symmetrical ureas including heterocyclic moieties. 16 Another strategy to increase the solubility is to increase the carbon bond saturation, defined by fraction sp³ (Fsp³), which has correlated with improved solubility, and even with the higher development stage along the drug discovery pipeline. 17 As spirocyclic scaffolds dramatically increase Fsp³, polar spirocyclic scaffolds were successfully employed as the basis for sEH inhibitor design.…”
Section: Introductionmentioning
confidence: 99%
“…Isocyanates are strategically important substrates in the synthesis of amides [ 1 3 ], polyurethanes [ 4 6 ], urethanes [ 7 ] and ureas, including those with biological activity [ 8 11 ]. Adamantane-containing isocyanates are initial substrates in the synthesis of asymmetric ureas, which act as effective inhibitors of human soluble epoxide hydrolase (human sEH) [ 12 15 ], an enzyme playing an important in the metabolism of epoxidated fatty acids. Urethanes derived from adamantan-1-yl isocyanate can act as potential acetyl- and butyrylcholinesterase inhibitors [ 16 ] and exhibit antimicrobial activity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%